Development of ecotourism potential in Sambori Tribe, Bima, West Nusa Tenggara, Indonesia - Zulharman Zulharman; Mochamad Noeryoko; Ibnu Khaldun (Journal of Applied Sciences in Travel and Hospitality, 2021)
The purpose of this research is to explore the potential of ecotourism that can be developed in Sambori Tribe, Bima. Besides, to identify the right strategy for developing ecotourism on family medicinal plants in Sambori Tribe based on community and stakeholder perceptions. The research method used was descriptive methods with survey and observation techniques. The study using purposive sampling to get the correct data. The data is in the form of local herbal products developed into tourism destinations and economic benefits that are to improve the economic welfare of marginalized communities. Aspects of the development include flora in the form of herbs, fauna, natural attractions with a view of the mountains with cool air. in addition, this herbal plant can improve the accessibility and socio-cultural life of the community. Furthermore, the improvement of quality of life in Sambori, Bima is carried out through herbal obar plants to improve the quality of healthy life as well as an area with the potential of herbal plant ecotourism. It has a diversity of flora and fauna potentials as well as a very suitable landscape potential as a tourist attraction. The result of the study found that Sambori Tribe has the potential of flora and fauna and the landscapes.Public health development strategies in the future, not only can be done in hospitals, it can also be done at home through live pharmacies based on medicinal family plants that can be used as an improvement of public health, economy and ecotourism in the Sambori Tribe. in addition, with the potential of live pharmacies, will have an impact on the appeal of high biological nature with a beautiful natural panorama.